The relationship between previous lower extremity injury, body weight and bilateral eccentric hamstring strength imbalance in young soccer players - Isik, A.; Unlu, G.; Gozubuyuk, O. B.; Aslanyurek, T.; Bereceli, C. (Montenegrin Journal of Sports Science and Medicine, 2018)
This study aims to investigate the effect of lower extremity (LE) injuries on bilateral hamstring eccentric strength imbalance (HSI) and to determine the relationship between body weight (BW) and HSI in young male soccer players. Eighty-eight young soccer players aged 14-19 in Turkey voluntarily participated in this study. Eccentric hamstring strength measurements were taken using a NordBord® Hamstring Testing Device. To obtain the LE backgrounds of the participants, individual interviews were administered to the players, and the obtained data were verified through a review of previous injury records. While 22 (25%) out of 88 players reported LE injuries in the previous two years (injured players (IP)), the rest of them (75%) did not report any LE injuries (non-injured players (NP)). HSI values as peak forces were computed by extracting the weaker leg values from the stronger leg values. Both the Analysis of Variance (ANOVA) and the Analysis of Covariance (ANCOVA) were performed, controlling the BW effect in order to test the effects of LE injuries on HSI. Correlation analysis was also conducted, taking into consideration the previous research findings on the relationship between body weight and strength variables. There was significant relationship between BW and HSI ((p r >0.02)) and non-significant results for HSI (F (1.85) =0.578, p>0.05). However, the effect of BW was significant for HSI (F (1.85) =3.91,